Miicro biology : an introduction - Gerard J Tortora; Case, Christine L; Bair, Warner B III; Weber, Derek; Funke, Berdell R (London Pearson, 2025)
Tortora/Case/Bair/Weber/Funke's Microbiology, An Introduction delivers an exceptionally clear presentation of complex topics, a careful balance of concepts and applications, and pedagogically superior art. With a focus on big-picture concepts and themes in microbiology, the text encourages you to visualize and synthesize more difficult topics such as microbial metabolism, immunology and microbial genetics. The trusted clinical focus and student-friendly narrative will help you understand why microbiology is relevant to your future healthcare career. The 14th Edition deepens the clinical focus and integrates SARS-CoV-2 and COVID-19 coverage throughout. Updates include innovative microbiology research, revised immunology chapters, and an extensive diversity, equity and inclusion review.
Keywords: Microbiology